Family and drugs: considerations of a sociologist - Burgalassi, Silvano (Medicina e Morale, 2024)
Modern reality and the realisation of the vastness and depth of social problems have long since oriented the great mass of scholars of the so-called 'human sciences' away from considerations pertaining to the social sphere and into that of macra processes.